2017
DOI: 10.1111/tid.12709
|View full text |Cite
|
Sign up to set email alerts
|

High‐dose calcineurin inhibitor‐free everolimus as a maintenance regimen for heart transplantation may be a risk factor for Pneumocystis pneumonia

Abstract: A high-dose CNI-free everolimus maintenance regimen might yield a higher incidence of post-transplantation PJP.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1

Citation Types

0
1
0

Year Published

2017
2017
2023
2023

Publication Types

Select...
5

Relationship

0
5

Authors

Journals

citations
Cited by 7 publications
(1 citation statement)
references
References 31 publications
0
1
0
Order By: Relevance
“…These infections occurred on everolimus therapy, several months after withdrawal of prophylaxis. The authors suggested that the high frequency of PJP infection might be attributed to the high everolimus dose and high serum trough concentration [35].…”
Section: Mechanistic Target Of Rapamycin Inhibitormentioning
confidence: 99%
“…These infections occurred on everolimus therapy, several months after withdrawal of prophylaxis. The authors suggested that the high frequency of PJP infection might be attributed to the high everolimus dose and high serum trough concentration [35].…”
Section: Mechanistic Target Of Rapamycin Inhibitormentioning
confidence: 99%